Revealed notions of distributive justice II: Experimental evidence - Nicole Becker; Kirsten Häger; Jan Heufer (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
We report the results of a combination of a dictator experiment with either a "social planner" or a "veil of ignorance" experiment. The experimental design and the analysis of the data are based on the theoretical framework proposed in the companion paper by Becker, Häger, and Heufer (BHH, 2013), in which we introduce a "notion of distributive justice" by which individuals trade off equality and efficiency. The purpose of the theoretical framework is to explain preferences in dictator experiments by a combination of selfishness and concerns for distributive justice. Most participants conform very well with the Agreement and Symmetry axioms proposed in BHH; we find that for 80% of participants the evidence is very strong. The experiment therefore demonstrates that most participants' behaviour in dictator experiments can be explained by a combination of selfishness and concerns for distributive justice. We also provide a rough classification of preferences and notions of distributive justice and show that participants' strength of the sense for justice (Karni and Safra 2002b) can be compared non- parametrically.
Keywords: C14; C91; D11; D12; D63; D64; 330; altruism; dictator games; distributive justice; experimental economics; non-parametric analysis; preference decomposition; revealed preference; social preferences